2017
DOI: 10.1111/cbdd.13084
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic interactions at the ligand–protein interface: Implications for the development of docking scoring functions

Abstract: The ability to design and fine-tune non-covalent interactions between organic ligands and proteins is indispensable to rational drug development. Aromatic stacking has long been recognized as one of the key constituents of ligand-protein interfaces. In this communication, we employ a two-parameter geometric model to conduct a large-scale statistical analysis of aromatic contacts in the experimental and computer-generated structures of ligand-protein complexes, considering various combinations of aromatic amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 72 publications
(123 reference statements)
2
84
0
Order By: Relevance
“…These essential Pi-alkyl bonds were observed in this study. Further the conformational stability of the protein-ligand interactions are derived from Pi-lone, Pi-anion and halogen non covalent interactions (Brylinski 2018;Arthur and Uzairu 2019;Belhassan et al 2019). In this study we observed Pi-sigma interaction in the interface of FtsZ-24284406; Pi-anion bond was observed in FtsZ-49671233 and FtsZ-24791139 complex and one fluorine bond was observed in FtsZ-49671233 complex.…”
Section: Discussionsupporting
confidence: 48%
“…These essential Pi-alkyl bonds were observed in this study. Further the conformational stability of the protein-ligand interactions are derived from Pi-lone, Pi-anion and halogen non covalent interactions (Brylinski 2018;Arthur and Uzairu 2019;Belhassan et al 2019). In this study we observed Pi-sigma interaction in the interface of FtsZ-24284406; Pi-anion bond was observed in FtsZ-49671233 and FtsZ-24791139 complex and one fluorine bond was observed in FtsZ-49671233 complex.…”
Section: Discussionsupporting
confidence: 48%
“…protein-drug complexes and protein/drugnucleic acid complexes, are well known in the literature. [41][42][43][44][45][46] Therefore, a more detailed analysis of these interactions was performed.…”
Section: Serotonin-receptor Local Non-covalent Interactionsmentioning
confidence: 99%
“…In general, the stability of the protein-ligand complex increases with the number of H-bonds for small molecules. However, for drug compounds with large molecular structures and high molecular masses, the stability of the protein-ligand adduct is greatly influenced by alkyl interactions and π -stacking interactions (hydrophobic) in addition to the conventional H-bonds [ 33 , 34 ]. Since the molecular sizes of the anti-HIV drugs are not too low or too high, both H-bond interactions and hydrophobic interactions play a significant role in the receptor-ligand complex formation.…”
Section: Resultsmentioning
confidence: 99%